The true identity of Tectaria nesiotica Holttum (Tectariaceae), with comments on the species identification in Pleocnemia (Dryopteridaceae) - Zhao, Hui-Guo; Dong, Shi-Yong (Phytotaxa, 2015)
The species Tectaria nesiotica Holttum, described from New Guinea, is confirmed to be a member of the genus Pleocnemia and thus a new combination, P. nesiotica, is proposed here. It superficially resembles some species of Tectaria with large, finely dissected fronds and with veins anastomosing only along costae but differs in venation pattern. Within Pleocnemia, P. nesiotica is readily distinguished from other species by the blackish rachis and the sori confined to the apex of pinnule lobes. We fail to provide a key to all known species of Pleocnemia from New Guinea because for this group the species concept is currently very confusing, which was probably resulted from the incomplete herbarium specimens and the overemphasis of the character, sori indusiate or not, in recognizing species. Field observations are called for the clarification of species boundary in Pleocnemia.